CORPUS LINGUISTICS – CONCEPT, APPROACHES, METHODS AND APPLICATIONS IN RESEARCH AND TEACHING OF GERMAN AS A FOREIGN LANGUAGE - Nga, Le Tuyet (VNU Journal of Foreign Studies; Vol 36 No 5DO - 10.25073/2525-2445/vnufs.4609, 2020)
The paper discusses the concept corpus (criteria for corpora, classification of the corpora), corpus linguistics as science or as methodology, approaches (corpus-based approach and corpus-driven approach), research methods (quantitative and qualitative) and tools used in corpus linguistics from the perspective of German scientists. One focus of the work lies in the discussion of the relationship between corpus linguistics and German as a foreign language and in the application possibilities of corpus linguistics for research and teaching of the German language.